Stimulation of the tibial nerve—a randomised trial for urinary problems associated with Parkinson's—the STARTUP trial. (15th June 2022) - McClurg, Doreen; Elders, Andrew; Hagen, Suzanne; Mason, Helen; Booth, Jo; Cunnington, Anne-Louise; Walker, Richard; Deane, Katherine; Harari, Danielle; Panicker, Jalesh; Stratton, Susan; McArthur, Jaclyn; et al.
Abstract: Background: non-motor symptoms such as bladder dysfunction are common (80%) in people with Parkinson's increasing the risk for falls with a negative impact on health-related costs and quality of life. We undertook STARTUP to evaluate the clinical and cost-effectiveness of using an adhesive electrode to stimulate the transcutaneous tibial nerve stimulation (TTNS) to treat bladder dysfunction in people with Parkinson's disease (PD). Study design, materials and methods: STARTUP was a parallel two-arm, multi-centre, pragmatic, double-blind, randomised controlled trial. Each participant attended one clinic visit to complete consent, be randomised using a computer-generated system and to be shown how to use the device. The trial had two co-primary outcome measures: International Consultation on Incontinence Questionnaire-Urinary Incontinence Short Form and the International Prostate Symptom Score (IPSS). These were completed at baseline, 6 and 12 weeks. A bladder frequency chart and resource questionnaire were also completed. Results: two hundred forty two participants were randomised. About 59% of participants were male, the mean age was 69 years and mean time since diagnosis was 6 years. Questionnaire return rate was between 79 and 90%. There was a statistically significantly lower score in the active group at 6 weeks in the IPSS questionnaire (mean difference (Standard deviation, SD) 12.5 (6.5) vs 10.9 (5.5), effect size −1.49, 95% CI −2.72, −0.25). There was no statistically significant change in any other outcome. Conclusion: TTNS was demonstrated to be safe with a high level of compliance. There was a significant change in one of the co-primary outcome measures at the end of the treatment period (i.e. 6 weeks), which could indicate a benefit. Further fully powered RCTs are required to determine effective treatments.